Khaled Abou El-Fadl dan Orientasi Humanistik Dalam Studi Fiqh - Abid Rohmanu (Justicia Islamica, 2011)
This paper intends to study towards a humanistic orientation of fiqh study. The study of fiqh based humanistic orientation aims to study fiqh with more emphatic on values and morality rather than legal-formal aspects. on the other side, this study will be the counter-part of the theocentric orientation of fiqh study. The theocentric orientation is shown to lose its elan vital, because it is more preoccupied with the issues of authenticity rather than social problems. This paper is attributed to Abou El Fadl, most noted for his scholarly approach to fiqh from moral point of view.